Classification of Industrial Robots According to the Number of Degrees of Mobility-structural Synthesis, Useful Configurations, Work Spaces and Kinematics - Staretu, Ionel (New Approaches in Engineering Research Vol. 1, 2021)
Serial industrial robots can be classified according to several criteria, the most important being: the number of mobility degrees or independent movements, the number of independent kinematic axis, the shape of the workspace, the value of the useful load, the precision of touching a predetermined point, etc. Among these criteria, the number of degrees of mobility directly determines the structure of the kinematic chain corresponding to the robot and implicitly its construction, functionality and utility. In this paper, we define the three classes of industrial serial robots according to the degree of mobility: the class of serial industrial robots of minimum configuration, the class of redundant serial industrial robots and the class of hyper-redundant serial industrial robots. For each class of serial industrial robots the structural synthesis method is presented and representative examples of structures are given. For two versions of redundant chain workspaces are represented, first sequentially, successively for each coupling, starting with the first coupling from the kinematic chain base and then the workspace is represented totally by overlapping workspaces obtained for each coupling. We present the direct kinematics analysis for kinematic chain with 6 and 8 axis using the homogeneous operators’ method too.